Implementasi Program Bilingual untuk Mengembangkan Kecerdasan Verbal Linguistik Anak di SDIT Al-Azhar Kediri - Inni Nikmatul Aolia; Makhromi Makhromi (Indonesian Journal of Humanities and Social Sciences, 2020)
This study explains the development of language as a means of communication between people in the world because mastery of foreign languages is an urgent demand for today's era. Bilingual programs are the ability to use two languages, not only in speaking and writing but also the ability to understand what other people communicate verbally and in writing. This research was conducted using descriptive qualitative research with the aim of describing the phenomena that exist in the research location. The data collected by researchers is through observation, interviews, documentation, data analysis, data reduction, display data, and conclusion drawing/verification. The findings of this study confirm that; the application of the bilingual program is applied when teaching and learning take place supported by bilingual activities including flashcards, English conversation book, English and Arabic camp, English and Arabic day, and reading.